Development of Voice Recognition Door Lock with Keypad - Ikhbal Khan, Aasraffiqh; FATIMAH BINTI MOHAMMED YUSOP, (Progress in Engineering Application and Technology, 2023)
Significant advances in wireless sensor networks, telecommunications, and informatics have enabled pervasive intelligence, which envisions the future Internet of things (IoT). A door access system's development includes a wide range of features, from a simple keypad to the complex use of and biometrics. The door access system was developed to address the issue of burglary by increasing the security of the access system. The study concentrated on residents of standard homes. As a result, voice recognition door locks with keypad have been developed to address the issue of a vulnerable access control system. The goal of this research is to create a prototype of a voice recognition door lock with a keypad, code the prototype, and then test the prototype for accuracy. The prototype was created using the Arduino microcontroller, which comes with its own programming language and electronic development and testing platform. A keypad and voice recognition were used as inputs for the project, and a solenoid door lock and an LCD display were used as outputs. The prototypes were subjected to functional and accuracy tests in order to collect data and determine their proper function. Through the use of a simple Arduino approach, this project provides a dependable solution for improving door access security. The prototype had a 86.67% successful rate of recognising the first command and a 93.33% successful rate of recognising the second command, according to the results of the accuracy testing performed on 10 different individuals in this study.